Black Sea Visions in the Lyric of Hristo Fotev - Gołek-Sepetliewa, Dorota (Poznańskie Studia Slawistyczne, 2024)
The purpose of this article is to interpret the semantic dominants in the lyrics of the Bulgarian writer Hristo Fotev, which deal with the diverse visions of the Black Sea coast, Burgas, the port, the inhabitants, the newcomers, and the sea waters. The analysis includes selected poems from the following volumes: Ballad Journey (1961), Lyrics (1965), Sentimental Dedications (1967), and Collected Works. Vol. 1: Poetry (1998). Attention is focused on the subjective identification with place and strategies for creating symbolic, metaphorical, imaginary, geographical, and historical space and its maritime elements. The seaside landscape becomes the inspiration for the poetic imagination, at the same time constituting the object of lyrical creation. Images of the sea also become a probe into the poet’s mental state, the individual elements of the maritime landscape being a metaphor for human experience. In the ballad convention, the sea takes on fantastic, supernatural, mysterious qualities and is the place of existence of mythical characters.